Systematic revision of the South American “Nuncia” (Opiliones, Laniatores, Triaenonychidae) - Lourenco Porto, Willians (2024)
The genus Nuncia has long been the most speciose within the Opiliones family Triaenonychidae, comprising 63 species and subspecies distributed across New Zealand and South America. Recent molecular studies utilizing Sanger sequencing and ultraconserved elements (UCEs) have indicated that this genus is not monophyletic, and true Nuncia are actually confined to New Zealand. Here, the morphology of all South American triaenonychids is re-examined and DNA sequence data compiled from three markers (18S rRNA, 28S rRNA and cytochrome c oxidase subunit I) for a large number of triaenonychid species, including specimens from all areas with species currently and formerly classified in Nuncia to reassess their phylogenetic position. Based on our findings we 1) revalidate the genus Chilenuncia (Muñoz-Cuevas, 1971) nom. rest.; 2) describe five new genera: Fresiax gen. nov., Mistralia gen. nov., Laftrachia gen. nov., Lautaria gen. nov., Nerudiella gen. nov.; 3) redescribe five species: Fresiax spinulosa comb. nov., Mistralia verrucosa comb. nov., Chilenuncia chilensis comb. nov., Chilenuncia rostrata comb. nov., Nerudiella americana comb. nov.; and 4) describe 22 new species of South American triaenonychids: Fresiax conica sp. nov., Fresiax fray sp. nov., Fresiax mauryi sp. nov., Fresiax pichicuy sp. nov., Mistralia ramirezi sp. nov., Laftrachia robin sp. nov., Lautaria ceachei sp. nov., Nerudiella cachai sp. nov., Nerudiella caramavida sp. nov., Nerudiella cautin sp. nov., Nerudiella choapa sp. nov., Nerudiella curi sp. nov., Nerudiella goroi sp. nov., Nerudiella jaimei sp. nov., Nerudiella malleco sp. nov., Nerudiella penco sp. nov., Nerudiella pichi sp. nov., Nerudiella portai sp. nov., Nerudiella quenes sp. nov., Nerudiella vilches sp. nov., Nerudiella wekufe sp. nov., and Nerudiella zapallar sp. nov. Furthermore, we provide detailed illustrations of all the South American species belonging to these lineages formerly classified in Nuncia.